Database Management System and Types of Build Architecture - Deeksha, Sandeep Mogha (Mathematical Statistician and Engineering Applications, 2022)
We are living in a world of data. Data is the lifeblood of any organization. Whether it’s used for decision-making or to provide a service, data plays a vital role in the success of any business. It can provide insights into how customers are behaving, what products are most popular, and where the business needs to adapt to improve. In a sense, data is the foundation upon which organizations are built. Data architecture is often overlooked as a critical component of a successful data system, but data systems are prone to failure without a sound, well-designed architecture. Users at the bottom tier interact with the database through a web interface or API. Users at the next tier up interact with the database through an application programming interface (API). And finally, users at the top tier interact with the database through a thick client. This separation of tiers helps to optimize access to data and to provide high availability, even in the event of a failure of the web tier. We present the introduction to DBMS architecture and each type along with some advance methods. Here, we have also discuss about the proposed cloud DBMS architecture. This paper reviews the databases developed so far and some traditional databases applications.